Assessment of Antioxidant Properties in Fruits of Myrica esculenta: A Popular Wild Edible Species in Indian Himalayan Region. (17th March 2011) - Rawat, Sandeep; Jugran, Arun; Giri, Lalit; Bhatt, Indra D.; Rawal, Ranbeer S.
Abstract : Crude extract of Myrica esculenta fruits, a wild edible species of Indian Himalayan Region, was evaluated for phenolic compounds and antioxidant properties. Results revealed significant variation in total phenolic and flavonoid contents across populations. Among populations, total phenolic content varied between 1.78 and 2.51 mg gallic acid equivalent/g fresh weight (fw) of fruits and total flavonoids ranged between 1.31 and 1.59 mg quercetin equivalent/g fw. Antioxidant activity determined by 2, 2′-azinobis(3-ethylbenzothiazoline-6-sulphonic acid) radical scavenging, 1, 1-diphenyl-2-picrylhydrazyl radical scavenging and ferric reducing antioxidant power (FRAP) exhibited considerable antioxidant potential and showed significant positive correlation with total phenolic and total flavonoids content. High performance liquid chromatography analysis revealed significant variation ( P <  .01) in phenolic compounds (i.e., gallic acid, catechin, hydroxybenzioc acid and ρ -coumaric acid) across populations. This study provides evidences to establish that consumption of M. esculenta fruits while providing relished taste would also help in reduction of free radicals. Therefore, this wild edible species deserves promotion in the region through horticulture and forestry interventions.